PERENCANAAN STRUKTUR GEDUNG 3 LANTAI ASRAMA MAHASISWA (RUSUNAWA) PUTRI II UNIVERSITAS PGRI SEMARANG MENGGUNAKAN METODE SRPMM (SISTEM RANGKA PEMIKUL MOMEN MENENGAH) - Khobad, Andrian Majid; Ardian, Muhammad Ryan; Husodo, Ibnu Toto; Rizani, Mohammad Debby (Jurnal Teknik Sipil Giratory UPGRIS, 2022)
AbstractThe 3 Floor Student Dormitory Building (Rusunawa) daughter II University of PGRI Semarang was built in the 4th campus area of Universitas PGRI Semarang with a building area of 2119 m2. The building is planned based on the results of the Cone Penetration Test (CPT), it is known that the building is built on soil with soft soil conditions (SE site class). The calculation of the structure uses the SRPMM method (medium moment resisting frame system) which refers to SNI 1726-2019: Earthquake Resistance Planning Procedures for Building and Non-Building Structures. Meanwhile, non-earthquake loading can be adjusted to SNI 1727-2013: Minimum Load for Design of Buildings and Other Structures. The secondary structure is in the form of plates and stairs which are carried by the primary structure, namely beams, columns and shear walls. The lower structure consists of sloof and pile cap, with drill pile foundation. TheÂ main ingredient of the structure is reinforced concrete, with reference to SNI 2847- 2019: Requirements for Structural Concrete for Buildings and Explanations. In the requirements of the SRPMM method the structural components that are considered are columns, beams, beam-column relationships and plates. In this case the building structure can respond to earthquakes with seismic design categories (KDS) A, B, and C, without collapsing. The results of the calculation of the primary structure and the substructure of the building are applied in technical drawings consisting of architectural drawings, structural plans, and detailed reinforcement drawings.Keywords: building, medium moment resisting frame system, earthquake load.